Pengaruh Budaya Pamer (Flexing) di Media Sosial terhadap Kepuasan Diri (Qana’ah) Mahasiswa IAIN Parepare - Nur Atiqa A; St. Nurhayati; Kasmia Arifin; Marseyla Marseyla; Nur Annisa; Multazam Nur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of digital technology and social media has triggered changes in students' social behavior, particularly through the emergence of a showing-off culture (flexing) that is increasingly prevalent across various platforms. As active social media users, students are frequently exposed to content showcasing luxurious lifestyles, achievements, and status symbols, influencing their views on standards of happiness and life success. This exposure fosters social comparison and the formation of an excessive self-image in the digital realm, potentially leading to consumptive behavior and psychological stress. From an Islamic perspective, the value of qana'ah (contentment) emphasizes acceptance and sufficiency, yet this value has not been fully internalized in students' lives, including those at IAIN Parepare. Prior literature indicates that social media use correlates with decreased subjective well-being and heightened social comparison tendencies, while showing-off behavior serves as a means for social recognition but contributes to dissatisfaction. This study aims to analyze the influence of the showing-off culture on social media on the contentment levels of IAIN Parepare students. The method employs a sociological approach combined with quantitative methods via a survey technique using questionnaires from 103 respondents, analyzed through statistical techniques. The results reveal that the showing-off culture on social media significantly affects students contentment levels, thus accepting the proposed hypothesis (H1) and rejecting H0. This confirms that the intensity of the showing-off culture is a significant factor influencing contentment among students.